World War One and Authoritarian Thought in the Lusophone World - Martinho,Francisco Carlos Palomanes (2017)
The goal of this article is to analyze the impacts of Portugal's participation in the First World War, especially emphasizing the construction of an authoritarian, conservative, and anti-republican culture policy. It also tries to understand the polarization process of the Portuguese Army between the conflict and the coup d'etat on 28 May, 1926.